Pharmacological Aspects of Neuro-Immune Interactions - Tarasov, Vadim V.; Kudryashov, Nikita V.; Chubarev, Vladimir N.; Kalinina, Tatiana S.; Barreto, George E.; Ashraf, Ghulam M.; Aliev, Gjumrakch (Current Pharmaceutical Design, 2018)
The use of systematic approach for the analysis of mechanism of action of drugs at different levels of biological organization of organisms is an important task in experimental and clinical pharmacology for drug designing and increasing the efficacy and safety of drugs. The analysis of published data on pharmacological effects of psychotropic drugs possessing immunomodulatory and/or antiviral properties have shown a correlation between central effects of examined drugs associated with the impact on the processes of neurogenesis of adult brain and survival of neurons, and their ability to alter levels of key proinflammatory cytokines. The changes that occur as a result of the influence of pharmacological agents at one of the systems should inevitably lead to the functional reorganization at another. Integrative mechanisms underlying the neuro-immune interactions may explain the
Keywords: panavir